Revalorización del conocimiento ancestral para la elaboración de fariña en la comunidad nativa Kukama Kukamiria, San José de Lupuna, Iquitos 2021 - Aliaga Flores, Araceli Lucero (2023)
The research "Revaluation of ancestral knowledge for the elaboration of fariña in the Native Community Kukama Kukamiria San José De Lupuna, Iquitos", aimed to describe the process of revaluation of ancestral knowledge for the elaboration of fariña, the qualitative approach was used, which which reflects the daily life of the population involved, the context and the sociocultural dynamics around the elaboration of the fariña. Likewise, it is of a descriptive type and ethnographic design. The population is a total of 180 families and as shown 40 families. Techniques such as semi-structured interview and participant observation were applied. As results, it is presented that the elaboration of the fariña constitutes a participatory process, the applied knowledge allows to strengthen the sense of belonging and the revaluation process is developed within the framework of the strengthening of the collective identity. It concludes that the fariña preparation procedure is associated with the farm through family work and techniques that are transmitted from generation to generation. On the other hand, there are beliefs to plant cassava associating it with the moon season and the entry of new tools allows strengthening the elaboration process generating an integration with ancestral knowledge; Likewise, there is an opening to the market making visible the importance of the fariña of San José de Lupuna that not only rescues knowledge, but also strengthens family work and allows them to generate economic income.